Pendampingan Memandikan dan Mengkafani Jenazah pada Siswa SMK Anwarul Maliki Sukorejo Kabupaten Pasuruan - askhabul kirom (Institute for Research and Community Service in Universitas Yudharta Pasuruan, 2019)
SMK Anwarul Maliki Sukorejo is a Vocational High School based on Anwarul Maliki Sukorejo Islamic boarding school. The pesantren, known as the Anwarul Maliki pesantren, is one of the Islamic boarding schools in Sukorejo Pasuruan. The author takes the service in the form of training assistance for bathing and dressing the corpse which is attended by Anwarul Maliki Vocational School students so that they can become knowledge, understanding, and skills on how to take care of the corpse. The training activities for the washing and washing of the bodies of the Anwarul Maliki Vocational School students went well as planned. Factors that support the smooth running of activities are full support from the school, the cohesiveness of SMK Anwarul Maliki Sukorejo students.